메타버스기반의 온라인 교육 플랫폼 활용 가능성 연구 - 예술교육 중심으로 - 고사양(Si-Yang Gao); 윤영두(YoungDoo Yoon) (한국콘텐츠학회 논문지, 22(7), 2022)
Online education is a major trend in the future education change and the COVID-19 pandemic has further accelerated the process. Online education has become an important part of the modern education system because of its stability and continuity. However, the disadvantages of traditional online education can reduce users' experience, thus upgrading online education is the key to future education. Metaverse, as a new platform for online education, redefines the occurrence space of online education, changes the teaching mode and learning and evaluation methods of online education, and shows its development potential. This research analyzed the characteristics of Metaverse and its technological development status, and then proposed an intelligent online education environment construction scheme based focused on Metaverse of art education. 온라인 교육은 미래 교육 변혁의 큰 흐름으로, 2020년 이래의 코로나19 사태는 이 변혁의 진행 과정을 더욱 가속화 시켰다. 온라인 교육은 안정성과 연속성 측면에서 현대 교육시스템의 중요한 부분으로 자리 잡았다. 그러나 전통적인 온라인 교육은 오프라인 교육에 비하여 상호작용과 학습 몰입감에 대한 문제점이 지적되고 있다. 또한 예술실기 수업이면 사용자의 체험감이 떨어지기 때문에 온라인 교육을 업그레이드하는 것이 미래 온라인 교육의 관건으로 대두되고 있다. 메타버스 플랫폼을 기반으로 하는 온라인 교육은 온라인 교육의 발생 공간을 재정의하고, 온라인 교육의 교수 모델과 학습 및 평가 방식을 변화시켜 발전 잠재력을 보여 주고 있다. 본 연구에서는 먼저 메타버스의 특징과 그 기술 발전에 대한 현황분석, 예술교육 중심으로 메타버스에 기초한 스마트 온라인 교육환경 구축 방안을 제시하고자 한다.